2017
DOI: 10.4236/ojcm.2017.73008
|View full text |Cite
|
Sign up to set email alerts
|

On the s<sup>±</sup>-Wave Superconductivity in the Iron-Based Superconductors: A Perspective Based on a Detailed Study of Ba<sub>0.6</sub>K<sub>0.4</sub>Fe<sub>2</sub>As<sub>2</sub> via the Generalized-Bardeen-Cooper-Schrieffer Equations Incorporating Fermi Energy

Abstract: Guided by the belief that Fermi energy E F (equivalently, chemical potential μ) plays a pivotal role in determining the properties of superconductors (SCs), we have recently derived μ-incorporated Generalized-Bardeen-Cooper-Schrieffer equations (GBCSEs) for the gaps (Δs) and critical temperatures (T c s) of both elemental and composite SCs. The μ-dependent interaction parameters consistent with the values of Δs and T c s of any of these SCs were shown to lead to expressions for the effective mass of electrons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This becomes cumbersome if one is simultaneously dealing with more than one such equation. The operator Re provides a much simpler, one-step, alternative, as was also noted in the context of Fe-based World Journal of Condensed Matter Physics SCs [23]. This remark also applies to (39).…”
Section: Discussionmentioning
confidence: 69%
“…This becomes cumbersome if one is simultaneously dealing with more than one such equation. The operator Re provides a much simpler, one-step, alternative, as was also noted in the context of Fe-based World Journal of Condensed Matter Physics SCs [23]. This remark also applies to (39).…”
Section: Discussionmentioning
confidence: 69%
“…The salient superconducting properties of Ba 0.6 K 0.4 Fe 2 As 2 , which are generic of the Fe-based SCs (also called iron-pnictide SCs), are as follows (for sources of these properties, see [31]): (i) Superconductivity in this SC is due to the s AE -wave state, which signifies that a gap below the Fermi surface and the one corresponding to it above the Fermi surface, Δ h and Δ e , respectively, has opposite signs. By adopting the framework of GBCSEs as outlined above, it has been shown in [31] that one can quantitatively explain all the above features of Ba 0.6 K 0.4 Fe 2 As 2without invoking a new superconducting state for the SC. This is an important remark because, on the basis of the multiband approach, it has been suggested in a recent review article [32] that superconductivity in Fe-based SCs is manifestation of a new state.…”
Section: Fe-based Scsmentioning
confidence: 99%
“…It has been shown that [6], A more accurate (but rather elaborate) equation that additionally contains E F explicitly has been derived in [8]; the values of y obtained via these equations differ significantly only when μ/kθ ≈ 0.3 or less.…”
Section: Critical Current Density J0 Of An Sc At T = 0 Via Ca In the mentioning
confidence: 99%
“…Gleaned from [1], summarized then are the reasons for its wide adoption. In Section 3, based on [4] [5] [6] [7] and [8], is…”
Section: Introductionmentioning
confidence: 99%